Climate change impact on the dispersion of airborne emissions and the resulting separation distances to avoid odour annoyance. (April 2019) - Piringer, Martin; Knauder, Werner; Anders, Ivonne; Andre, Konrad; Zollitsch, Werner; Hörtenhuber, Stefan J.; Baumgartner, Johannes; Niebuhr, Knut; Hennig-Pauka, Isabel; Schönhart, Martin; Schauberger, Günther
Abstract: In a changing climate it is expected that the predicted temperature rise will also affect wind conditions and parameters needed to determine atmospheric stability. In this paper we investigate how the changes in wind conditions and stability will affect the dispersion of airborne emissions. For odorous substances, the separation distances around livestock farms are calculated to protect the neighbourhood from odour annoyance. This is done for two Central European sites in Austria with different meteorological conditions, situated in areas with considerable livestock activity, namely around Wels in the north-alpine foreland and at Feldbach in the Raab valley south of the Alpine chain. Two climate scenarios have been used, namely the time period 1981–2010 (present climate) and the period 2036–2065 (future climate). Slight changes in wind and stability conditions for the two sites have been obtained, influencing the changes in separation distances. Although these are only minor, they show some interesting differences not expected a priori. We conclude that the climate change signal has mostly only a low impact on the separation distances. This will not substantially affect the zoning and licensing of livestock buildings in Austria in the course of this century. Highlights: Climate change has an impact on dispersion parameters. Impact on dispersion parameters is site-dependent. A slight increase of the separation distances is to be expected in the future.